Molarsys SSI application development to improve students' critical thinking and argumentation on the reproductive system topic - Ratu Tasya Tazkia; Agung Wijaya Subiantoro (Universitas Muhammadiyah Malang, 2025)
Socioscientific issue (SSI)-based learning media has shown potential in improving students’ critical thinking and argumentation skills. However, mobile learning applications that integrate SSI specifically for reproductive system learning in senior high school biology remain limited. This study aimed to develop a Molarsys SSI-based mobile learning application to improve critical thinking and argumentation skills of senior high school students in Phase F. This research employed a development research design using the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model. The research subjects consisted of media and biology education experts, biology content experts, biology teachers, and eleventh-grade science students divided into an experimental class and a control class, with 35 students in each class. Data were collected using essay test instruments and non-test instruments, including needs analysis sheets, feasibility assessment sheets by media and material experts, and practicality assessment sheets. Data analysis was conducted descriptively and using inferential statistics through independent sample t-tests. The results indicated that: (1) the Molarsys application is feasible for learning reproductive system material; (2) the application is practical for use in senior high school biology learning, and (3) the application is effective in improving students’ critical thinking skills and argumentation abilities on reproductive system material.